2012
DOI: 10.1021/jp2115065
|View full text |Cite
|
Sign up to set email alerts
|

Design of Coupled Porphyrin Chromophores with Unusually Large Hyperpolarizabilities

Abstract: A new series of push−pull porphyrin-based chromophores with unusually large static first hyperpolarizabilities are designed on the basis of coupled-perturbed Hartree−Fock and density functional calculations. The proper combination of critical building blocks, including a ruthenium(II) bisterpyridine complex, proquinoidal thiadiazoloquinoxaline, and (porphinato)zinc(II) units, gives rise to considerable predicted enhancements of the static nonlinear optical (NLO) response, computed to be as large as 11 300 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…[45][46][47][48][49][50][51] Conjugated porphyrin dimers exhibit much larger third-order susceptibilities (g) than the corresponding porphyrin monomers, [49][50][51] thus Equation (3) implies that dimeric analogues of JR1 will display even higher sensitivities to electric field. Previous studies on voltagesensitive SHG dyes have focused entirely on styryl and retinal chromophores.…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] Conjugated porphyrin dimers exhibit much larger third-order susceptibilities (g) than the corresponding porphyrin monomers, [49][50][51] thus Equation (3) implies that dimeric analogues of JR1 will display even higher sensitivities to electric field. Previous studies on voltagesensitive SHG dyes have focused entirely on styryl and retinal chromophores.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the molecular classes whose first hyperpolarizabilities are studied. In each case, the base molecule is shown, and the class is defined by varying the number of repeat units, n. The calculation of the intrinsic first hyperpolarizability requires as an input the measured first hyperpolarizability, the effective number of electrons, N , and the energy difference between the ground and first electronic excited states, E 10 , so that Equation 3 can be evaluated using Equation 1.…”
Section: Approachmentioning
confidence: 99%
“…For example, Therien and coworkers reported a series of (porphinato)zinc(II)‐based chromophores featuring nitrothiophenyl and nitrooligothiophenyl electron‐accepting moieties which were proven to exhibit large NLO responses through hyper‐Rayleigh light scattering (HRS) measurements . Jiang et al theoretically designed a series of push–pull porphyrin‐based chromophores including ruthenium(II) bisterpyridine complex and nitro end group linked through phenylacetylene bridge exhibiting unusually large static first hyperpolarizabilities . Sukegawaa et al found the electron transfer process can be finely tuned based on the ZnP‐π‐bridge‐C 60 models by replacing different types of π‐bridges .…”
Section: Introductionmentioning
confidence: 99%